Investigation of a cost-effective strategy for polymer electrolyte membrane fuel cells: High power density operation - Zhou, Jieyang; Seo, Bongjin; Wang, Zhe; Wang, Yun (International journal of hydrogen energy, 2021)
Polymer electrolyte membrane (PEM) fuel cell technology needs to overcome the cost barrier in order to compete with the internal combustion engines (ICEs) for transportation application. A viable approach is to raise fuel cell's power output without increasing its size and Pt loading in the catalyst layers (CLs). In this strategy, the cost per kW power output can be proportionally reduced due to the increased power density. This paper examines this strategy by exploring several important aspects that influence fuel cell performance under high power or current density using a three-dimensional (3-D) fuel cell model. It is shown that local CLs may be subject to low oxygen concentration under a high current density of 2 A/cm2, causing low reaction rate near the outlet, especially under the land. Additionally, the oxygen reduction reaction (ORR) rate may be subject to a large through-plane variation under 2 A/cm2, raising ohmic voltage loss in the CL. Two additional cases are investigated to improve fuel cell performance under 2 A/cm2: one has a 5 times thinner CL with the same ORR kinetics per membrane electrode assembly (MEA) area and the other has a 5 times thinner CL with 5 times higher ORR kinetics. The results show the output voltage is raised approximately from 0.5 V to 0.554 V in the former CL case and further to 0.606 V for the latter CL. To enable high-efficiency operation (e.g. >50%), thinner CLs with high ORR kinetics and GDLs with better transport properties are one research and development (R&D) direction. •Fuel cell operation may subject to oxygen starvation near cathode outlet @ 2.0 A/cm2.•The oxygen reduction reaction (ORR) rate subjects to large spatial variations in all the three dimensions @ 2.0 A/cm2.•GDLs with better transport properties are desirable for high current density operation.•Thinner catalyst layers with high ORR kinetics are desirable for high current density operation.